VAN GÖLÜ'NDEN ENERJİ ÜRETİMİ - ŞENGÜLER, SEZA (Fırat Üniveristesi, 1991)
In this study, it has been undertaken the problem of how to produce energy from one of the largest lakes of the world, Lake Van. Lake Van has a 3700 km2, area and a 1 648 m. altitude. A couple of HPP 'Hydroelectric Power Plants' and dams on the main branches of River Dicle which is located in the soutwest of the lake, 8re already under construction. According to the annual reports, the annual changing of the water-level of the lake is about 50 cm. Almost all of the this amount of water loses by evaporating. It is thought that, the evaporated water could be taken for use in energy production. At the end of all researches, the most suitable place of taking out the water is near Tatvan. Also, most suitable and nearest place for out let is near Regulator Bitlis, which is on Bitlis Stream and has a 1 239 m. altitude. In this area. Van HPP which has a distance 22 km. from the intake, will be conctructed. The water, which is taking from near Tatvan, is brought with a pllery to the HPP Van. Following this, it will flow through the Stream Bitlis, will pass through HPP Bitlis and than will reach Dam Baykan. Later on, the water will come to llisu Dam and than will arrive at Dam Cizre. Than it will leave the country borders with its own flow. Naturally, the water quantity, which is taking from the lake and leaving country borders, will supply the energy production with its falling altitude. In our calculations, amount of this energy is about 4.69 billion kWh. Key Words : Lake Yan, energy production, HPP, dams, kWh.

ÖZET YÜKSEK Lisans Tezi VAN GOlO'NDEN ENERJİ ÜRETİMİ Seza ŞENGÜLER Fırat Üniversitesi Fen Bilimleri Enstitüsü İnşaat Mühendisliği Anabilim Dalı 1991, Sayfa: 58 Bu çalışmada, dünyanın en büyük göllerinden biri olan Van Gölü'nden nasıl enerji üretileceği problemi irdelenmektedir. Van Gölü, 3700 km2, yüzölçümüne ve 1648 m. denizden yüksekliğe sahiptir. Gölün güneybatısında bulunan Dicle Nehri'nin ana kollan üzerindeki HES "Hidroelektrik Santrallar" ve barajların çalışmaları devam etmektedir. Yıllık raporlara göre, göldeki yıllık su seviyesi değişimi 50 cm. civarındadır. Yaklaşık olarak bu miktar buharlaşmayla kaybolmaktadır. Buharlaşan bu suyun enerji üretiminde kullanılabileceği düşünülmektedir. Araştırmalar sonucunda, en uygun su alma yeri Tatvan yakınlarıdır En uygun ve en yakın su götürme yeri de 1 239 m. kotunda, Bitlis çayı üzerindeki Bitlis Regülatör ü'nün yakınlarıdır. Bu bölgede, su alma yerinden 22 km. uzaklıkta Van HES kurulacaktır. Tatvan yakınlarından alman su, galeri ile Van HES'ne getirilecektir. Buna müteakip Bitlis Çayı "m takip ederek Bitlis HES'ne geçecek ve sonra Baykan Barajı'na varacaktır. Daha sonra, su llısu Barajı'na gelecek ve ardından Cizre Barajı'na erişecektir. Sonra kendi akışıyla ülke sınırlan m terkedecektir. Doğal olarak, gölden alınan ve ülke sınırlarım terkeden bu su miktan, düşü yükseklikleri ile enerji üretimini sağlayacaktır. Yaptığımız hesaplarda, bu enerji miktarı, yaklaşık olarak 4.69 milyar kWh. tir. ANAHTAR KELİMELER: Van Gölü, enerji üretimi, HES, barajlar, kWh.
Producing energy from Lake Van
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Enerji; Energy